-2(1-6r)=-2+4r

Simple and best practice solution for -2(1-6r)=-2+4r equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(1-6r)=-2+4r equation:


Simplifying
-2(1 + -6r) = -2 + 4r
(1 * -2 + -6r * -2) = -2 + 4r
(-2 + 12r) = -2 + 4r

Add '2' to each side of the equation.
-2 + 2 + 12r = -2 + 2 + 4r

Combine like terms: -2 + 2 = 0
0 + 12r = -2 + 2 + 4r
12r = -2 + 2 + 4r

Combine like terms: -2 + 2 = 0
12r = 0 + 4r
12r = 4r

Solving
12r = 4r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-4r' to each side of the equation.
12r + -4r = 4r + -4r

Combine like terms: 12r + -4r = 8r
8r = 4r + -4r

Combine like terms: 4r + -4r = 0
8r = 0

Divide each side by '8'.
r = 0

Simplifying
r = 0

See similar equations:

| 4v+6=41-3v | | 4s+14=2s+66 | | 3x^2+6x=168 | | p+p+64=180 | | -3(x-1)=-2x-3 | | 2a-21=a | | 12x-11y=23 | | 3/13=u/10 | | 5(2x+5)-1=-2x | | 2b-48+2b-96=180 | | 3u-64=u | | 10y+9=13y+3 | | 3n+4(5n+2)=8+3n | | 16z-21+2z+39=180 | | -3(1-5m)+4=1-2m | | 7=an-1+-15 | | 4c-65=5c-85 | | 4c-65=5c-68 | | -2+3p=6p-4-2p | | 7y+73=4y+94 | | -5+6m=5m-8 | | t=2t-51 | | 3y=-x-2 | | 4y-5x=4y-5x | | 8/9-5/6×1/3 | | 4b+64=2b+68 | | 8n-n=-4+6n | | 7c-77=4c-35 | | -4x+4=11+2x-7x | | 9x+16y=7 | | 2/y-3=3/y | | 3q+6=6q |

Equations solver categories